Cost-effective device to characterize phase change materials. (28th November 2019) - Mjallal, Ibrahim; Hammoud, Mohammad; Habchi, Charbel; Lemenand, Thierry
Abstract: Phase change materials (PCMs) have been an emerging research topic for the last few years. However, the lack of detailed and precise information regarding their thermophysical properties is a major concern for researchers. The current paper presents a simple method to determine the specific heat ( ), thermal conductivity and melting temperature ( ) of a PCM using a novel low-cost device. Compared to the conventional existing methods, such as differential scanning calorimetry (DSC), T-history, panel tests and simple thermal analyses, this new method grants the following features: simplicity and ease of manufacturing and the ability to measure the thermophysical properties of heterogeneous PCM samples without a reference material. Using this novel device, the thermophysical properties of sodium sulfate decahydrate were measured and good agreement is obtained with values collected from the open literature using other devices.